Synthesis of pH-sensitive amphotericin B-poly(ethylene glycol) conjugates and study of their controlled release in vitro - Sedlák, Miloš; Pravda, Martin; Štaud, František; Kubicová, Lenka; Týčová, Kateřina; Ventura, Karel (Bioorganic & medicinal chemistry, 2007)
New intravenous conjugates of amphotericin B (AMB) with poly(ethylene glycols) (PEG) (M=5000, 10,000, 20,000) have been synthesized and characterised. The intermediate PEGs possess a 1,4-disubstituted benzene ring with aldehyde group at the end of the chain. The benzene ring is connected with PEG at its 4-position (with respect to the aldehyde group) by various functional groups (ether, amide, ester). Reaction of terminal aldehyde group of the substituted PEGs with AMB gave conjugates containing a pH-sensitive imine linkage, which can be presumed to exhibit antimycotic effect at sites with lowered pH value. All types of the conjugates are relatively stable in phosphate buffer at physiological conditions of pH 7.4 (37 degrees C), less than 5 mol% AMB being split off from them within 24 h. For a model medium of afflicted tissue was used a phosphate buffer (pH 5.5, 37 degrees C), in which controlled release of AMB from the conjugates takes place. The imine linkage is split to give free AMB with half-lives of 2-45 min. The rate of acid catalysed hydrolysis depends upon substitution of the benzene ring; however, it does not depend on molecular weights of the PEGs used. The conjugates with ester linkage undergo enzymatic splitting in human blood plasma and/or blood serum at pH 7.4 (37 degrees C) with half-lives of 2-5 h depending on molecular weights of the PEGs used (M = 5000, 10,000, 20,000). At first, the splitting of ester linkage produces the relatively stable pro-drug, that is, 4-carboxybenzylideniminoamphotericin B, which is decomposed to AMB and 4-formylbenzoic acid in a goal-directed manner only at pH 7 (t1/2 = 2 min, pH 5.5, 37 degrees C). A goal-directed release of AMB is only achieved by acid catalysed hydrolysis of imine linkage, either from the polymeric conjugate or from the pro-drug released thereof. The LD50 values determined in vivo (mouse) are 20.7 mg/kg and 40.5 mg/kg for the conjugates with ester linkage (M = 10,000 and 5000, respectively), which means that they are ca. 6-11 times less toxic than free AMB.
Keywords: financování organizované; Animals; Amphotericin B; hydrolýza; Hydrogen-Ion Concentration; krev; amfotericin B; In Vitro Techniques; Polyethylene Glycols; techniky in vitro; lidé; Mice; Blood; spektrofotometrie ultrafialová; myši; Spectrophotometry, Infrared; polyethylenglykoly; Financing, Organized; hmotnostní spektrometrie s elektrosprejovou ionizací; Hydrolysis; Spectrophotometry, Ultraviolet; spektrofotometrie infračervená; zvířata; koncentrace vodíkových iontů; Spectrometry, Mass, Electrospray Ionization; Humans